Supplementation of Lactic Acid Bacteria in Feed Induced Non-Specific Immune Response of Tiger Grouper (SUPLEMENTASI BAKTERI ASAM LAKTAT PADA PAKAN MERANGSANG TANGGAP KEBAL NON SPESIFIK IKAN KERAPU MACAN) - ., Nursyirwani; Asmara, Widya; Wahyuni, Agnesia Endamg Tri Hastuti; ., Triyanto (Jurnal Veteriner, 2013)
Lactic acid bacteria (LAB) have an ability to enhance innate responses in fish. The aim of this studywas to study the effect of three LAB isolates (Kerapu Situbondo Usus: KSBU 12C, KSBU 5Da, and KSBU9 on non-specific immune responses of tiger grouper (Epinephelus fuscoguttatus). The fish were fed dietsupplemented with each of the bacterial isolates at final concentration of 108 CFU mL-1 twice every day.The haematology parameters (haematocrit, leucocyte count, heterophils/neutrophils, monocytes,lymphocytes), phagocytic activity and total LAB were measured every seven days. After 28 days, the fishwere challenged with Vibrio alginolyticus. During the feeding period, the haematocrit values of fish fed withLAB isolates were higher than those of control group, and values ranged from 24.67±8.33 % to 40.50±7.09%. The leucocyte counts increased, mainly after being challenged with V. alginolyticus, and the valuesranged from 40.33 ±6.03 × 1000 cell mL-1 to 139.33±15.57 × 1000 cell mL-1. With the exception oflymphocytes, proportion of heterophils and monocytes, and phagocytic activity were higher in fish fed withLAB isolates than those of control. The presence of LAB in the gastrointestinal tract of fish fed with LABresulted in higher haematology parameters and phagocytic activity in comparison to fish fed control diet.In conclusion, supplementation of LAB in diet could enhance non-specific immune response of tiger grouper.
Keywords: Tiger grouper, lactic acid bacteria, haematocrit, leucocyte, phagocytic activity